2018
DOI: 10.1186/s12916-018-1180-x
|View full text |Cite
|
Sign up to set email alerts
|

Global variation in bacterial strains that cause tuberculosis disease: a systematic review and meta-analysis

Abstract: BackgroundThe host, microbial, and environmental factors that contribute to variation in tuberculosis (TB) disease are incompletely understood. Accumulating evidence suggests that one driver of geographic variation in TB disease is the local ecology of mycobacterial genotypes or strains, and there is a need for a comprehensive and systematic synthesis of these data. The objectives of this study were to (1) map the global distribution of genotypes that cause TB disease and (2) examine whether any epidemiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 62 publications
9
68
0
Order By: Relevance
“…M. tuberculosis sensu stricto isolates from South Asia were dispersed across lineages 1-4 with an enrichment of lineages 1 and 3, which is concordant with previous reports ( 26 ). Cattle origin MTBC sequences deposited from South Asia were distributed among M. tuberculosis lineage 1 and M. orygis lineages, highlighting the need to understand pathogenicity and transmission dynamics of these pathogens in cattle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…M. tuberculosis sensu stricto isolates from South Asia were dispersed across lineages 1-4 with an enrichment of lineages 1 and 3, which is concordant with previous reports ( 26 ). Cattle origin MTBC sequences deposited from South Asia were distributed among M. tuberculosis lineage 1 and M. orygis lineages, highlighting the need to understand pathogenicity and transmission dynamics of these pathogens in cattle.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, Rahim et al suggested that the global distribution of these subspecies indicates the emergence of M. orygis prior to M. bovis from a common MTBC ancestor, wherein M. orygis may have been dispersed to South Asia with the migration of humans and become established before the arrival of M. bovis ( 14 ). However, prior establishment of an MTBC lineage does not negate the introduction of another at a later point in time, as is demonstrated by the wide dispersal of M. tuberculosis lineages 2 and 4 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our work also has incorporated other assumptions regarding the different virulence mechanisms between "ancient" and "modern" MtbC lineages in the knowledge that this is a question open to discussion. What is clear is the evidence for the higher dissemination ability of "modern" lineages compared with "ancient" ones 21 . The fact that the latter are restricted to specific geographical regions also points to some sort of genetic susceptibility linked to race/ethnic groups, as proposed by several authors 7,17,66 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the trade-off for "ancient" MtbC lineages is the higher probability of progression to active TB at a cost of being less able to disseminate through the population explaining why "ancient" lineages can only be found in certain geographical locations 21 . The fact that the appearance of "modern" lineages (46,000 BCE) coincided with a significant increase in the population (from 10 4 to 10 6 individuals) in Asia, while remaining constant in Africa (around 10 6 people) 22,23 , indicates that some sort of population explosion occurred in Asia before the Neolithic, as proposed by several authors [24][25][26] , giving support to its dissemination.…”
mentioning
confidence: 99%
“…It is widely recognized that Mycobacterium tuberculosis (Mtb) of different molecular types have different transmission capacities, pathogenicity and drug resistance rates [1,2]. Therefore, Mtb genotypes may be associated with the tuberculosis (TB) endemicity [3,4].…”
Section: Introductionmentioning
confidence: 99%